(untitled) (Annals of Medical Research, 2021)
Aim: First-line eradication therapy protocols for Helicobacter pylori infection and their success rates still prove to be matter of interest for researchers. The aim of this study was to examine retrospectively eradication therapy protocols used in patients infected with H. pylori in our region with high resistance to clarithromycin, compare success rates and determine the factors affecting success rates. Material and Methods: Eradication therapies for dyspeptic patients who were found to be Helicobacter pylori positive as revealed by upper gastrointestinal endoscopy and biopsy results and success rates attained in the microscopic examination of stool in the 4th week after the therapy were analyzed. Group 1 (legacy triple therapy): clarithromycin 500 mg film-coated tablet 2x1, lansoprazole 30 mg capsule 2x1, amoxicillin 1000 mg tablet 2x1, 14-day therapy period; Group 2 (bismuth-free quadruple therapy): clarithromycin 500 mg film tablet 2x1, rabeprazole 20 mg tablet 2*1, amoxicillin 1000 mg tablet 2x1, metronidazole 500mg 2x1 tablet, 14-day therapy period; Group 3 (bismuthal quadruple therapy): bismuth subsalicylate 262 mg tablet 2x2, metronidazole 500 mg tablet 3x1, tetracycline 500 mg capsule 3x1, pantoprazole 40mg tablet 2x1, 10-day therapy period.Results: Data of 168 patients were analyzed. The patients were divided into Group 1 (classical therapy) with 80 patients, Group 2 (bismuth-free quadruple therapy) with 46 patients and Group 3 (bismuthal quadruple therapy) with 42 patients. Eradication success rates were as follows: Group 1 (80%), Group 2 (80.4%) and Group 3 (83.3%).Conclusion: Antibiotic resistance is the sole reason for the low success rate in eradication therapy for Helicobacter pylori. In regions with high clarithromycin resistance bismuth-free quadruple therapy can be employed as an alternative. In regions with metronidazole resistance in addition to clarithromycin resistance bismuthal therapy protocols can be employed. Keywords: Helicobacter pylori; eradication therapy; clarithromycin resistance.